Informal Employment in the Siberia Village - ФадееваОльга Петровна (Journal of Economic Sociology, 2010)
The ten years of reforms in Post-Soviet Russia did not solve the problem of effective rural economy formation but led to the considerable worsening of socio-economic situation of the most part of the rural population. The market reorganization of the collective farms ended up with factual bankruptcy for many of them. Recent farmers lost the limited advantages of the Soviet period – stable employment in the collective farms and money payments. The changes in the agrarian sector of economy were the reasons for twoatfirstsightparadoxical phenomena. The first one is that workers do not get money payments for several years but still have the job position at economically poor farming enterprises. A sharp increase of the personal subsidiary plots production accounts for that they took the leading positions in meat and milk production in the country.